Lost in the stars : Kurt Weill and Maxwell Anderson's musical adaptation of Alan Paton's novel Cry the beloved country - Walton, Chris, 1963- (University of Pretoria, 2013)
Dissertation (MMus)--University of Pretoria, 2008.